Development of value added drinks from date palm juice (Phoenix sylvestris) - Faria Hossain Shanta (Elsevier, 2021)
The high decaying tendency of date palm juice limited its manifold application. Here, we developed a preservation technique for concentrated juice and formulated ready to serve (RTS) drinks. The collected date palm juice was heated at 85 °C for 5 min; scum was removed and preserved in the sterilized glass bottle. After that, this pasteurized juice was concentrated to 9%, 12%, 15%, 18% and 21% total soluble solids (TSS) levels and treated with 200 ppm of potassium metabisulfite (KMS) and stored at refrigerated temperature (4 °C). Among them, 18% TSS showed overall acceptability to sensory evaluations for colour, flavour, sweetness, TSS, acidity and microbial load. In contrast, heat treated date palm juice (9% TSS) was used to formulate RTS drinks containing 10%, 20%, 30% and 40% date palm juice, were preserved in sterilized bottles and stored at 30 °C. Results showed that RTS drinks containing 30% date palm juice secured the best colour, flavour, sweetness, TSS, acidity, microbial load and overall acceptability. Furthermore, no significant change was observed in TSS, acidity, microbial load up to three and six months for concentrated juice and RTS drinks, respectively.